2012
DOI: 10.1259/dmfr/51664704
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric potential and current on mandibular linear measurements in cone beam CT

Abstract: Objectives: The purpose of this study was to compare mandibular linear distances measured from cone beam CT (CBCT) images produced by different radiographic parameter settings (peak kilovoltage and milliampere value). Methods: 20 cadaver hemimandibles with edentulous ridges posterior to the mental foramen were embedded in clear resin blocks and scanned by a CBCT machine (CB MercuRay TM ; Hitachi Medico Technology Corp., Chiba-ken, Japan). The radiographic parameters comprised four peak kilovoltage settings (60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
2
9
1
Order By: Relevance
“…In consideration of the dose reduction, they suggested that 10 mA and 60 kV should be used. In the present study, our results were similar to those of Panmekiate et al 10 for clear MCs, but relatively higher voltages and currents were needed to see unclear MCs. Neves et al 32 acquired images with a scan time of 10.8 s at 60 kV, with seven different combinations of tube currents (2 mA, 4 mA, 6.3 mA, 8 mA, 10 mA, 12 mA and 15 mA).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In consideration of the dose reduction, they suggested that 10 mA and 60 kV should be used. In the present study, our results were similar to those of Panmekiate et al 10 for clear MCs, but relatively higher voltages and currents were needed to see unclear MCs. Neves et al 32 acquired images with a scan time of 10.8 s at 60 kV, with seven different combinations of tube currents (2 mA, 4 mA, 6.3 mA, 8 mA, 10 mA, 12 mA and 15 mA).…”
Section: Discussionsupporting
confidence: 92%
“…[6][7][8][9] However, the information it provides is only two-dimensional and the images are distorted, often resulting in miscalculation of the location of the MC. planning, 4,10,11 and both have recently been replacing conventional panoramic radiographs. 1 CBCT requires a lower exposure dose than CT 12,13 and provides adequate image quality at a lower cost and with fewer artefacts than CT. CBCT has therefore become the ideal pre-operative assessment tool for dental implant surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-dose protocols presented less significant differences (one of two comparisons and two of three for high-dose protocols). Our results differ from those of Panmekiate et al 17 On mandibular linear measurements, no significant differences in the distances were found between the different combinations of peak voltage and milliamperes. Using a human mandible cadaver, Hassan et al 14 showed CBCT scan mode (exposure time) was less relevant on root canal visibility.…”
Section: Discussioncontrasting
confidence: 99%
“…It may result in injury to the neurovascular bundle and cause some postoperative complaints such as neuroma, paresthesia, anesthesia and hemorrhage [4][5] . It has been stated that CBCT anatomical linear measurements are accurate and reliable [6][7][8][9][10][11][12][13] . However, the inclination of the patient's head during CBCT image acquisition can cause distortion in measurements for preoperative implant planning [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%